(untitled) (Physical Education, Health and Social Sciences, 2025)
This study provides a critical analysis of the status of child rights in Pakistan, focusing on the country’s obligations under international conventions—particularly the United Nations Convention on the Rights of the Child (CRC)—and the degree to which these obligations have been implemented within the domestic legal system. This research analyses the statistics indicating the situation of child rights and measures adopted to protect child rights with special reference to international obligations of Pakistan. The research also discusses the jurisprudence developed by Pakistani Courts regarding relevant domestic and international laws and concludes with suitable recommendations for robust legal policy to protect child rights in consonance with international obligations of Pakistan. The study reveals that although numerous legislative reforms have been introduced over the years, a consistent gap persists between legal promises and their enforcement. The research explores how Pakistani courts began to innovate a domestic jurisprudence that internalises international child rights standards. By systematically examining landmark judicial decisions, this study demonstrates that the judiciary has emerged as an instrumental actor in bridging normative international commitments with practical domestic enforcement, often compensating for legislative and administrative shortcomings. This judicial jurisprudence represents an emergent trend in Pakistan that redefines the role of courts in safeguarding vulnerable populations. The paper concludes by offering a set of context-specific legal and policy recommendations aimed at strengthening child rights protections in line with international best practices and advancing the harmonisation of Pakistan’s legal regime with its global commitments.